Are emotionally intelligent people less prejudiced? The importance of emotion management skills for outgroup attitudes - Makwana, Arti Purshottam; Dhont, Kristof; García-Sancho, Esperanza; Fernández-Berrocal, Pablo (Wiley, 2021)
People vary in their ability to understand, process, and manage information about one's own and others’ emotions, a construct known as Emotional Intelligence (EI). Past research highlighted the importance of EI in interpersonal relations as well as the key role of emotions underlying outgroup prejudice. Remarkably, hardly any research has investigated the associations between EI and outgroup prejudice. In three studies (total N = 922) conducted in Spain and the United Kingdom, we measured emotional intelligence using self-report and performance tests and prejudice toward a variety of outgroups. Results showed that those with stronger performance-based emotion management skills expressed lower generalized ethnic prejudice (Studies 1–3), more positive attitudes toward immigrants (Study 2a) and refugees (Study 2b), and less homophobic attitudes (Study 3). This negative association between emotion management and prejudice was found with different performance-based EI measures and held after controlling for self-perceived EI (Study 1) and self-reported abilities to regulate emotions (Study 3). Study 3 further demonstrated that higher empathy partly accounted for the association between emotion management and prejudice. The findings suggest that emotion management abilities play an important, but so far largely neglected role in generalized prejudice.
Keywords: Inteligencia emocional; Emotion regulation; Prejudice; Emotional intelligence